Issues Concerning Nominal Anchors for Monetary Policy - Mussa, Michael (IMF Working Papers; Working Paper ;, 1994)
This paper presents a selective survey of issues relevant to the choice of nominal anchors for monetary policy. Section I reviews long price-level histories for the United Kingdom and United States, which reveal that the price level behaved very differently following WWII in these countries than it had done in previous post-war experiences. In particular following WWII the responsibilities of monetary policy expanded to encompass a business- cycle stabilization role and the nominal anchor shifted from the fixed anchor or price-level stability to the moving anchor of inflation-rate stability. The remaining sections of the paper review some of the considerations that are relevant to setting the average inflation rate in countries without a fixed nominal anchor.